2014
DOI: 10.1161/jaha.114.001420
|View full text |Cite
|
Sign up to set email alerts
|

Platelet GpIbα Binding to von Willebrand Factor Under Fluid Shear: Contributions of the D'D3‐Domain, A1‐Domain Flanking Peptide and O‐Linked Glycans

Abstract: BackgroundVon Willebrand Factor (VWF) A1‐domain binding to platelet receptor GpIbα is an important fluid‐shear dependent interaction that regulates both soluble VWF binding to platelets, and platelet tethering onto immobilized VWF. We evaluated the roles of different structural elements at the N‐terminus of the A1‐domain in regulating shear dependent platelet binding. Specifically, the focus was on the VWF D′D3‐domain, A1‐domain N‐terminal flanking peptide (NFP), and O‐glycans on this peptide.Methods and Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…To elaborate on this concept, the authors also made anti-D′D3 monoclonal antibodies that sterically inhibit the A1 domain of VWF from binding platelet GpIbα in flow based assays. Additionally, to demonstrate the importance of structural features N-terminal to the A1-domain in regulating VWF-GpIbα binding, various mutants were created [20]. Functional studies performed with these constructs using microfluidics show that the D′D3 domain of VWF is a key regulator that inhibits the binding of platelet GpIbα to the VWF-A1 domain and thrombus formation under physiological shear.…”
Section: Platelet Gpibα-vwf Interactions Leading To Platelet Accumulamentioning
confidence: 99%
See 1 more Smart Citation
“…To elaborate on this concept, the authors also made anti-D′D3 monoclonal antibodies that sterically inhibit the A1 domain of VWF from binding platelet GpIbα in flow based assays. Additionally, to demonstrate the importance of structural features N-terminal to the A1-domain in regulating VWF-GpIbα binding, various mutants were created [20]. Functional studies performed with these constructs using microfluidics show that the D′D3 domain of VWF is a key regulator that inhibits the binding of platelet GpIbα to the VWF-A1 domain and thrombus formation under physiological shear.…”
Section: Platelet Gpibα-vwf Interactions Leading To Platelet Accumulamentioning
confidence: 99%
“…Depending on the nature of the measurements, these assays can monitor multiple output parameters including: immobilized platelet number and aggregate morphology, platelet activation via cell surface P-selectin, cell surface phosphatidylserine via Annexin-V measurements, fibrin formation and also local thrombin production [20, 43, 44]. Using blood from FVIII −/− mice or human blood supplemented with anti-FIXa aptamer, early studies by Ogawa et al [45] , showed that thrombus formation patterns in haemophilia are regulated by fluid shear.…”
Section: Microfluidic Devices For Measuring Bleeding Riskmentioning
confidence: 99%
“…An auto-inhibitory role in regulating the A1-GPIbα interaction might further be played by VWF's glycans, as suggested by several studies that showed that (partial) deglycosylation of VWF enhances binding to GPIbα (De Marco et al, 1985;Fallah et al, 2013;Madabhushi et al, 2014). Unfortunately however, the possible influence of glycans has only rarely been taken into consideration in studies investigating VWF's activation, so that insights into this subject are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the plusD'D3 construct lacked domains D4‐CK and was thus N‐terminally dimerized by intra‐dimer disulfides between the D'D3 domains. It could be argued that this difference partially contributed to the observed shielding effect of D'D3, but later on Madabhushi et al () showed the same effect also with C‐terminally linked dimers lacking D'D3. Additional evidence for a direct inhibition of the A1‐GPIbα interaction through D'D3 was provided by showing that the presence of isolated D'D3 domain peptides directly inhibited ristocetin‐stimulated platelet agglutination mediated by the C‐terminally dimerized ΔD'D3 construct (Ulrichts et al, ).…”
Section: Vwf A1 Domain Shielding By Intramolecular Interactionsmentioning
confidence: 99%
See 1 more Smart Citation